The erosion of childhood : child oppression in Britain, 1860-1918 - Rose, Lionel, 1944- (Routledge, 1991)
Discusses the status of children in society from the mid-Victorian period to the end of the First World War, showing that children were regarded principally as objects to be used and abused rather than people in their own right.